Upaya Meningkatkan Motivasi Belajar Siswa pada Pembelajaran PAI Melalui Metode Karya Wisata Religi - Ilham Majid (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The lack of learning motivation of Madrasah Ibtidaiyah Darussalam students Regency towards PAI lessons causes their learning outcomes to be less than optimal. Low learning motivation, lack of commitment and responsibility as well as active participation of students in responding to learning are obstacles in achieving learning success. To overcome these problems, Islamic Religious Education Learning requires innovative strategies to motivate students to learn. One method that can be used is religious tourism, which combines learning with direct experience at historical and religious sites. This research is a literature study which aims to analyze efforts to increase student learning motivation in PAI learning through religious field trips. In this research, literature was searched and analyzed related to the concept of learning motivation, PAI learning and religious tourism work methods. The results of the literature study show that the religious field trip method can increase students' learning motivation through direct experience and enrich their understanding of Islamic teachings and spiritual values.